Picturing the Past: Gender in National Geographic Reconstructions of Prehistoric Life. Issue 1 (20th January 2013) - Solometo, Julie; Moss, Joshua
Abstract: Artistic reconstructions of ancient life are powerful blends of archaeological interpretation and imagination. Like other narratives about the past, they can project contemporary gender roles and relations on ancient peoples, and can reinforce or transform ideas about gender in the present. This article examines the construction of gender ideologies in National Geographic illustrations of prehistoric life. Our analysis of 204 pictorial reconstructions from 1936 to 2007 reveals that women and women's work are significantly underrepresented and undervalued, while exhibiting evidence of temporal change in response to societal factors and editorial influences. A vigorous archaeology of gender has had little impact on the magazine's imagined past; in some respects, the ancient women depicted in the last twenty years are just as scarce, passive, and subordinate as they were in the postwar "backlash" of the 1950s.